Comparative analysis of the transcriptional profile of the sugarcane smut pathogen during the interaction with resistant and susceptible genotypes - Bombardelli, Renato Gustavo Hoffmann (2020)
The sugarcane smut pathogen, Sporisorium scitamineum, is a dimorphic and biotrophic fungus, host-dependent to its sexual reproduction. The disease spread across all the sugarcane producing countries, except in Fiji, the group of volcanic islands in the South Pacific island in Oceania, causes economic losses reducing the yield. During the later years, the Genomics Group at ESALQ/USP has been extensively studying the sugarcane-smut interaction, considering its various aspects, including the pathogen attack mechanisms and plant defense responses. The pathogens secrete molecules known as effectors to modulate plant physiology, counterattack, and protect themselves against the plant host\'s defense barriers. In this work, we predicted the secretome and candidate effectors of the S. scitamineum. We used the RNA-Seq technique to determine the expression profile and compare the colonization of two sugarcane genotypes with contrasting resistance levels (smut-resistant, SP80-3280 and -susceptible, IAC66-6) 48 hours after inoculation. In the first chapter, we provided a brief review of the sugarcane smut disease. The second chapter contains the study providing data analysis of the transcriptome of S. scitamineum when infecting two contrasting sugarcane genotypes 48 hours after inoculation and a comparison with previous data of S. scitamineum growth in axenic culture. We found compelling results considering genes\' expression profile of the fungus infecting resistant and susceptible sugarcane genotypes. The pathogen expressed more peroxidases, including the catalases KatE and KatG, when infecting the resistant genotype, consistent with the early defense response involving reactive oxygen species (ROS) production by the SP80-3280 genotype. We revealed the variant expression of candidate effectors genes in each of the treatments, identifying promising candidates for further functional studies. Exploring the genes related to mating/filamentation growth, a crucial phase in the early infection stage, leading to the formation of the infective dikaryotic hyphae, we unveil the expression of genes of the cAMP/PKA pathway in S. scitamineum. Together with the REDOX equilibrium (production/detoxification of hydrogen peroxide), the fungus requires the expression of mating-related genes for successful infection. Herein we provided insights into the differential infection of resistant and susceptible sugarcane genotypes by the smut pathogen, suggesting some candidate genes for further functional characterization studies to increase this pathosystem\'s comprehension.